2019
DOI: 10.1002/edn3.20
|View full text |Cite
|
Sign up to set email alerts
|

Great Lakes Cladophora harbors phylogenetically diverse nitrogen‐fixing microorganisms

Abstract: Nitrogen‐fixing microorganisms are among the epiphytic communities in Cladophora, potentially benefitting the algae in nutrient‐deficient waters, but their abundance and diversity remain unexplored. In this study, we determined the abundance and taxonomic composition of these nitrogen‐fixing microorganisms in Cladophora growing on rocks, breakwall structures, or submerged dreissenid mussel beds around southern Lake Michigan (N = 33) during the summer 2015, using two complementary genomic techniques: quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The relative abundance of Devosia, another Gram− bacterium, was also increased in the HM samples, with members of this taxon known to tolerate brackish conditions [70]. Devosia can be associated with green algae which is consistent with its increased abundance as the chl a levels increased 3.4-fold, serving as a diazotroph by fixing nitrogen, but it can also facilitate the maintenance of ion homeostasis, which may be significant in the mixed salts of the "eco-friendly" de-icer [71,72]. Since members of Devosia can be halophilic and this genus was found at the highest relative abundance in the HM samples, we cannot exclude that it too was a contaminant in the M de-icer formulation.…”
Section: Shifts In Microbiota At High Concentrations Of "Eco-friendly...supporting
confidence: 58%
“…The relative abundance of Devosia, another Gram− bacterium, was also increased in the HM samples, with members of this taxon known to tolerate brackish conditions [70]. Devosia can be associated with green algae which is consistent with its increased abundance as the chl a levels increased 3.4-fold, serving as a diazotroph by fixing nitrogen, but it can also facilitate the maintenance of ion homeostasis, which may be significant in the mixed salts of the "eco-friendly" de-icer [71,72]. Since members of Devosia can be halophilic and this genus was found at the highest relative abundance in the HM samples, we cannot exclude that it too was a contaminant in the M de-icer formulation.…”
Section: Shifts In Microbiota At High Concentrations Of "Eco-friendly...supporting
confidence: 58%
“…In addition to the abundance of denitri cation functional genes, our CAP model revealed that the abundance of nitrogen xation gene (nifH) had a signi cant impact on the pattern of microbiome structures. Nitrogen xation is an energy-intensive process that typically occurs in N-de cient environments [10,56]. In this study, minimal nitrogen concentration was observed at the treatment outlet during low-ow seasons (e.g., 0.7 to 4.5 mg L -1 ), most likely due to the N removal by denitri cation and other anaerobic processes such as anammox.…”
Section: Discussionmentioning
confidence: 68%
“…The adoption of remediation programs and nutrient reduction policies, such as the European Green Deal and the Mississippi River Hypoxia Task Force [7,8], has created strong incentives for mitigation efforts. However, the anthropogenic inputs of nutrients, especially nitrogen and phosphorus, into watersheds still pose an imminent threat to global water quality [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Algal structural features, wide distribution, and ecological importance made the Cladophora microbiome a popular research topic during the past decade. Microbiome studies of the freshwater lacustrine Cladophora were conducted for algal samples collected from many locales, e.g., [4,6,[9][10][11][14][15][16][17][18][19][20]. However, the microbiomes of freshwater Cladophora living in lotic water bodies have not been investigated.…”
Section: Introductionmentioning
confidence: 99%